Strategi Penyajian Menu Mie Instan dalam Layanan Sarapan terhadap Kepuasan Tamu di Hotel Neo Malioboro - Priyanto Priyanto; Suparwi Suparwi; Denny Asmara (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2026)
Competition in the hospitality industry encourages hotels to present service innovations that are able to increase guest satisfaction, one of which is through the presentation of breakfast menus. This study aims to analyze the implementation of Standard Operating Procedure (SOP) for the presentation of Indomie menus with the concept of Live Cooking Stations, guest perception of the service, and its contribution to guest satisfaction at Hotel NEO Malioboro Yogyakarta. The research uses a qualitative approach with a descriptive method. Data was collected through observations, in-depth interviews with the Executive Chef Cluster and the Food and Beverage Manager Cluster, as well as documentation in the form of guest reviews on digital platforms. Data analysis uses the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawing by triangulating sources to ensure data validity. The results of the study show that the SOP for serving the Indomie menu has been implemented in a standardized manner starting from the mise en place stage, the live cooking process, to the presentation according to time, temperature, and dosage standards. The concept of a Live Cooking Station provides a more interactive breakfast experience through the flexibility of topping selection and direct interaction between guests and staff. Guest perceptions of the service show a positive response reflected in online reviews, guest comment cards, and direct feedback. The presentation strategy contributes to increasing guest satisfaction as well as becoming a unique selling point that strengthens the competitiveness of Hotel NEO Malioboro Yogyakarta in Food and Beverage Services.